2012
DOI: 10.1186/1746-6148-8-42
|View full text |Cite
|
Sign up to set email alerts
|

Transmissibility of caprine scrapie in ovine transgenic mice

Abstract: BackgroundThe United States control program for classical ovine scrapie is based in part on the finding that infection is typically spread through exposure to shed placentas from infected ewes. Transmission from goats to sheep is less well described. A suitable rodent model for examining the effect of caprine scrapie isolates in the ovine host will be useful in the ovine scrapie eradication effort. In this study, we describe the incubation time, brain lesion profile, glycoform pattern and PrPSc distribution pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Although the incubation periods in P1 Tg338 mice were prolong and variable for 3 caprine scrapie inocula, incubation periods in P2 mice were short and very similar. 21 Furthermore, brain lesion profiles 21 and PrP Sc accumulation levels in P2 mice were very similar ( Fig. 2A).…”
Section: Cprk13 Cells Support Propagation Of Tg338 Mouse-passaged Prnmentioning
confidence: 77%
See 4 more Smart Citations
“…Although the incubation periods in P1 Tg338 mice were prolong and variable for 3 caprine scrapie inocula, incubation periods in P2 mice were short and very similar. 21 Furthermore, brain lesion profiles 21 and PrP Sc accumulation levels in P2 mice were very similar ( Fig. 2A).…”
Section: Cprk13 Cells Support Propagation Of Tg338 Mouse-passaged Prnmentioning
confidence: 77%
“…13,24 The ability of RK13 cells to propagate prions upon expression of exogenous PrP C from multiple species 12,13,16,17 clearly confirmed that RK13 cells have the required cellular machinery for efficient prion propagation. Although PRNP haplotype 3 and 4 caprine scrapie inocula were able to produce clinical scrapie in recipient goats 9 and Tg338 mice 21 which was very similar to PRNP haplotype 1 and 2 caprine scrapie inoculated animals, the lack of scrapie prion propagation in cpRK13cells when inoculated with the same PRNP haplotypes 3 and 4 scrapie inocula highlight the possible involvement of other unidentified factors to establish successful infection.…”
Section: Cprk13 Cells Support Propagation Of Classical Caprine Scrapimentioning
confidence: 98%
See 3 more Smart Citations